The Relationship Between Mother's Occupation and Exclusive Breastfeeding at the Posi Posi Community Health Center - Nurbaya Tehuayo; Anik Sri Purwanti (Green Health International Journal of Health Sciences Nursing and Nutrition, 2025)
Background: Exclusive breastfeeding is a crucial factor in improving infant growth and health during the first six months of life. However, the achievement of exclusive breastfeeding is often influenced by various maternal factors, including the mother’s occupation. Working mothers frequently face challenges related to time constraints, workplace support, and breastfeeding facilities, which may affect their ability to provide exclusive breastfeeding. Understanding the relationship between maternal occupation and exclusive breastfeeding is essential to improve breastfeeding promotion programs at primary health care levels. Objective: This study aimed to determine the relationship between mother’s occupation and exclusive breastfeeding at the Posi Posi Community Health Center. Methods: This study employed an analytical observational design with a cross-sectional approach. The sample consisted of 30 mothers who had infants aged 6–12 months, selected using a total sampling technique. Data were collected through structured questionnaires and maternal health records. Statistical analysis was performed using the Wilcoxon test to examine the relationship between mother’s occupation and exclusive breastfeeding practices. Results: The results showed a statistically significant relationship between mother’s occupation and exclusive breastfeeding practices. The Wilcoxon test analysis obtained a p-value of 0.001 (p < 0.05), indicating that maternal occupation significantly influenced the provision of exclusive breastfeeding at the Posi Posi Community Health Center. Conclusion: There is a significant relationship between mother’s occupation and exclusive breastfeeding. Working mothers tend to experience more barriers in providing exclusive breastfeeding compared to non-working mothers. Strengthening workplace support, breastfeeding-friendly policies, and continuous health education is recommended to improve exclusive breastfeeding coverage.